Rekomendasi Tempat Wisata Kota Malang Menggunakan Metode Profile Matching Dan Saran Rute Menggunakan Floyd Warshall Berbasis Android - Alfian Chairi; Rekyan Regarsari Mardhi Putri; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Tourism has become an industry that provides great results for a region. So that the tourism object needs to be developed to get maximum results. There are various influences from the development of tourism, one of which is the economic improvement of the people around the place of tourism. Malang City is one of the cities that have various tourism and become a popular place to be targeted by people who live in East Java area in particular. However, because of the number of tours into its own problems for tourists to take decisions. Tourism recommendation decisions are seen from various factors, such as; The ticket price, the distance of the tour from the user's current location in the form of maps, facilities. Profile Matching is a decision-making mechanism by assuming that there is an ideal level of predictor variable that must be met by the subjects studied, rather than the minimum level to be met or skipped. In addition to assisting in the determination of the path will be used floyd-warshall method. So the process of determining the path of the maps will be assisted by floyd-warshall. For Core Factor is the criteria (competence) that is most important or prominent or most needed by an assessment that is expected to obtain optimal results while for secondary factor is a supporting factor that is less needed by an assessment. For perenkingan use 60% for core factor and 40% for secondary factor generate a 75% derivative rate.